PENGEMBANGAN MODEL BLENDED LEARNING BERBASIS LEARNING MANAGEMENT SYSTEM DI MTS. MUHAMMADIYAH SANINGBAKAR SOLOK - Muhammad Adri; Titi Sriwahyuni; Ika Parma Dewi (Universitas Negeri Padang, 2017)
Blended learning is one of model for integration of pedagogic and information and communication technology (ICT) skill of teacher. The community service program aims are to develop an integrated learning environment using Learning Management Sytem and incraasing teacher skill on utilize of ICT as a supporting tool to quality improvement of teaching and learning process at MTs. Muhammadiyah Saningbakar. The ICT skill as well as define on National Curriculum Nasional 2013 become an integrated skill for every teacher. In this programme, two focus activity are defined, first activity is redesign ICT training for teaching and second is development an online learning environment based-on learning management system (LMS) as delivery medium on blended learning. Redesign ICT training including some of main competencies are 1) Course material development, 2) Word Processing, 3) Presentation design, 4) content development, 5) online learning and 6) applied strategic of blended learning. Those skill is needed to fullfill of successfullness requirement of blended learning. Development an online learning management system is using most popular open source course LMS named by Moodle. To achieve development goal some activity is applied as folows : 1) Define an domain name system for MTs. Muhammadiyah Saningbakar, 2) Get a hosting services as online storage for online environment, 3) LMS installation and Configiration, 4) User management, 5) Course and teacher settings and 6) Content uploading and delivery using LMS. Blended learning environment is developed based on MTs. M curriculum, and defined on course setting of LMS into 3 catagories : Islamic, Adaptive, and Subtantive. And each category containing some course which are available on LMS and accessed by student using networking. Keyword: Blended Learning, ICT Skill, Integrated Learning Environment, LMS, Online Learning